Transformative Learning in Field Education: Students Bridging the Theory/Practice Gap. (20th August 2020) - Archer-Kuhn, Beth; Samson, Patricia; Damianakis, Thecla; Barrett, Betty; Matin, Sumaiya; Ahern, Christine
Abstract: In a four-year, four cohort study utilising a series of six focus groups, forty Masters of Social Work students preparing to graduate defined their personal and professional experiences of transformation in their respective social work field education settings. Using an inductive thematic analysis, students highlighted four key themes in their transformative learning (TL) process: (i) defining the nature of disorienting dilemmas in field education; (ii) critical self-reflection, coping and moving through disorienting dilemmas; (iii) identifying the transformative outcomes in a field context; and (iv) facilitative factors to TL in field education. The findings illuminate the essential role of the field supervisor in creating 'relationship'. The field supervisor/student relationship is the conduit to students' deep learning, critical reflection, identity shifts and empathy supporting the student's navigation through their disorientating moments towards transformative and meaningful outcomes. This study extends our understanding of the role of TL theory within experiential learning contexts and the feasibility of its use in the social work field education experience.